The Village Security Information System (Siskamling) to Support Digital Village Development - Hendrawan, Jodi; Perwitasari, Ika Devi; Ritonga, Ristra Sandra (International Conference on Sciences Development and Technology, 2022)
The process of disseminating information on environmental security or patrol schedules, information about events in the village community as well as information on important situations occurring in Klambir Lima Kebun village, the delivery process of which is carried out by attaching the patrol schedule to security posts or village offices, information dissemination is sometimes still word of mouth. word of mouth and the public often miss the latest environmental information. The conventional method would be better if it was proposed to design an information system that could be used as a place for information related to environmental safety that can be accessed anytime and anywhere by the community. The web-based environmental security information system (SISKAMLING) in its design uses UML (Unifield Modeling Language) which describes a responsive system that will greatly support the process of accessing information about environmental security in the village of Klambir Lima Kebun. The web is a means of sharing information digitally. The web is one of the media that really supports human life, especially in today's internet era.